Implementation of Independent Curriculum Management in Optimizing Fikih Learning at Purbalingga State Madrasah Aliyah - Mahmudah, Annisa; Hanif, Muh. (Matan : Journal of Islam and Muslim Society, 2025)
The implementation of the Independent Curriculum is a process of applying learning that focuses on flexibility in learning, and the active role of students as the center of learning activities, by integrating Islamic values, character building, and competencies comprehensively, by the principles of the Pancasila Student Profile. This study aims to describe the implementation of the Independent Curriculum in fikih education at the State Senior High School in Purbalingga, as well as to identify various challenges and strategies employed by teachers in adapting to the new learning approach. The research method used is qualitative, utilizing data collection techniques that include interviews, observations, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion. Data validity was tested using triangulation techniques. Based on the research results, it was found that the implementation of the Independent Curriculum in fikih education has driven a shift in teaching approaches toward a more student-centered approach, with a focus on character development, understanding of material relevant to daily life, and increased active student participation in learning. However, limitations in resources and teachers' knowledge of the essence of the independent curriculum remain the main challenges. Therefore, ongoing training and strengthening the role of teachers as facilitators in adaptive and transformative fikih learning are necessary.